Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1007/s005340050044
|View full text |Cite
|
Sign up to set email alerts
|

A new in-vitro drug sensitivity test (collagen-gel droplet embedded-culture drug sensitivity test) in carcinomas of pancreas and biliary tract: possible clinical utility

Abstract: The collagen-gel droplet embedded-culture drug sensitivity test (CD-DST), a chemosensitivity test, evaluate the efficacy of anticancer drugs and to was used clinically to thus plan rational postoperative chemotherapy for patients with pancreatic and biliary tract carcinomas. The CD-DST solves some problems inherent in other conventional assays. This method: (1) allows evaluation of four chemotherapeutic agents, using small quantities of cells (1 x 10(5) cells), (2) shows high primary culture success rates, (3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Results of in vitro drug sensitivity testing in the study laboratories, using the collagen gel droplet-embedded culture drug sensitivity test, have shown the efficacy of 5-FU and MMC to be 18.8% and 25.0%, respectively, in patients with pancreatic carcinoma and 50.0% and 50.0%, respectively, in patients with biliary tract carcinoma, indicating the particularly good sensitivity of biliary tract carcinoma to these agents. 29 In in vitro experiments, biliary tract carcinoma demonstrated a higher sensitivity to these agents compared with pancreatic carcinoma. Our group also has performed two randomized controlled studies of nonresected pancreaticobiliary carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Results of in vitro drug sensitivity testing in the study laboratories, using the collagen gel droplet-embedded culture drug sensitivity test, have shown the efficacy of 5-FU and MMC to be 18.8% and 25.0%, respectively, in patients with pancreatic carcinoma and 50.0% and 50.0%, respectively, in patients with biliary tract carcinoma, indicating the particularly good sensitivity of biliary tract carcinoma to these agents. 29 In in vitro experiments, biliary tract carcinoma demonstrated a higher sensitivity to these agents compared with pancreatic carcinoma. Our group also has performed two randomized controlled studies of nonresected pancreaticobiliary carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, chemosensitivity testing for treatment of gastric cancer has been approved in Japan. However, for pancreatic cancer, only one study has reported the use of chemosensitivity testing for adjuvant chemotherapy [12]. The most important reason that chemosensitivity testing has seldom been performed for pancreatic cancer is that many patients are unresectable.…”
Section: Introductionmentioning
confidence: 98%
“…The collagen gel droplet-embedded culture drug sensitivity test (CD-DST) is an in vitro anticancer drug sensitivity test [1][6]. Recent studies have reported that CD-DST can provide useful therapeutic information for patients with gastric cancer, lung cancer, colorectal cancer or pancreatic cancer [7][12].…”
Section: Introductionmentioning
confidence: 99%